Application of Rapid Application Development Method in WEB-Based Social Assistance Data Collection System in Lombu Village - Lende, Erniati; Neno, Friden Elefri; Ate, Paulus Mikku (Informatik : Jurnal Ilmu Komputer, 2025)
The process of collecting social assistance data in Lombu Village has been done manually, which has led to various problems such as duplicate data, delays in reporting, and inaccuracy in targeting recipients. To overcome these problems, this study aims to develop a web-based social assistance data collection information system that can improve efficiency, accuracy, and transparency in data management. The system development method used is Rapid Application Development (RAD), which emphasizes speed in development and direct user involvement in the system design and evaluation process. The research stages include needs identification, system design with users, prototype development, system testing, and feedback-based evaluation. Data was collected through interviews, observations, and documentation of the ongoing data collection process. The result of this research is a web-based system that is capable of storing, updating, and displaying beneficiary data in a structured manner and can be accessed by village officials with a simple and easy-to-use interface. System trials show that the system can facilitate data management and accelerate the social assistance reporting process at the village level.